Motor performance of fundamental skills of scholars of both sexes in Elementary School - Borges Neto, Juscelino de Souza (2021)
The objective of this paper is to determine how is the global motor performance and fundamental motor skills of elementary school students in general and compared between genders. This cross-sectional study evaluated the motor performance of schoolchildren aged 7 to 10 years old. Weight and height were measured, the socioeconomic class and routine of the participants were determined, and motor performance was assessed using the Test of Gross Motor Development – ​​3 (TGMD-3). Were adopted the measures of large motor quotient, gross overall score and subtest, measured by skills, in addition to qualitative analysis. The overall motor performance of students is below expectations for their age, especially in ball skills. Emphasis for girls who were worse than boys, more specifically on skills to dribble and kicking a stationary ball. It concluded that the stimuli received by children throughout life, especially with manipulative activities, including in physical education classes, were not enough to develop the children's fundamental motor skills.